2005
DOI: 10.1081/ja-200066736
|View full text |Cite
|
Sign up to set email alerts
|

Party Drugs: Properties, Prevalence, Patterns, and Problems

Abstract: This review summarizes the latest literature on "party" or "club" drugs, defined as MDMA, GHB, ketamine, and Rohypnol, as published from 2002 to early 2005. Club drugs have been categorized as being used at raves and dance parties. The literature shows that each drug has different properties, users, and settings. Each drug has different adverse effects and requires different acute care protocols. Although these drugs were identified early, scientific information about them, including the toxicological tests to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
85
0
8

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(98 citation statements)
references
References 138 publications
5
85
0
8
Order By: Relevance
“…On the contrary, Barra Funda and República that were not typically high HDId districts had higher rates probably due to the existence of a high number of nightclubs. These results confirmed that the well-known typical settings of ecstasy use are dance clubs and rave parties (Gahlinger, 2004;Maxwell, 2005). Data from a Brazilian survey also showed that 95.2% of 1.140 participants answered that party and/or club environment led to the consumption of ecstasy (Almeida, GarciaMijares, Silva, 2009).…”
Section: Discussionsupporting
confidence: 68%
“…On the contrary, Barra Funda and República that were not typically high HDId districts had higher rates probably due to the existence of a high number of nightclubs. These results confirmed that the well-known typical settings of ecstasy use are dance clubs and rave parties (Gahlinger, 2004;Maxwell, 2005). Data from a Brazilian survey also showed that 95.2% of 1.140 participants answered that party and/or club environment led to the consumption of ecstasy (Almeida, GarciaMijares, Silva, 2009).…”
Section: Discussionsupporting
confidence: 68%
“…These harms, although somewhat recognised in the broader literature [4][5][6][7], are not typically identified in popular harm reduction messages. Harm reduction messages that focus on risk of overdose and blood borne virus transmission, although potentially relevant to injecting drug users, are likely to be meaningless to recreational drug users.…”
Section: Discussionmentioning
confidence: 99%
“…Results from the current investigation provide information on the use of rohypnol which is one of the popularly abused drugs but with limited experimental information on effects and consequences of use especially on metal and social health [27]. Further investigations into the use and circumstances surrounding such instances; as well as the possible neurological consequences of rohypnol will be very useful in managing its effects and controlling its abuse.…”
Section: Biochemicals Functional Integritymentioning
confidence: 99%